2007
DOI: 10.1007/s10495-007-0132-2
|View full text |Cite
|
Sign up to set email alerts
|

Role of E-cadherin in the induction of apoptosis of HPV16-positive CaSki cervical cancer cells during multicellular tumor spheroid formation

Abstract: Multicellular tumor spheroids (MCTS) are three dimensional cell culture systems induced by suspension culture. MCTS are widely used in cancer research because of their similarity to solid tumors. CaSki cells are derived from a metastatic cervical cancer containing human papillomavirus 16 (HPV16). Cell death of CaSki cells in MCTS has been previously reported, and our model is used to better characterize the mechanisms of cell death of HPV16-positive keratinocytes. In this study, we found that apoptosis of CaSk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…This 100-kDa fragment, which was previously identified in prostate epithelial cells upon experimental calpain activation, is known to lack the capacity to bind to ␤-and ␥-catenin, in contrast to the full-length form of the protein (74). Moreover, in multicellular tumor spheroids (82) and in lymphovascular tumor emboli (71), the 100-kDa E-cadherin fragment was also discovered and attributed to endogenous activity of calpain (71). Another important finding of our study was the appearance of a 75-kDa ␤-catenin fragment under suspension culture conditions.…”
Section: Discussionmentioning
confidence: 94%
“…This 100-kDa fragment, which was previously identified in prostate epithelial cells upon experimental calpain activation, is known to lack the capacity to bind to ␤-and ␥-catenin, in contrast to the full-length form of the protein (74). Moreover, in multicellular tumor spheroids (82) and in lymphovascular tumor emboli (71), the 100-kDa E-cadherin fragment was also discovered and attributed to endogenous activity of calpain (71). Another important finding of our study was the appearance of a 75-kDa ␤-catenin fragment under suspension culture conditions.…”
Section: Discussionmentioning
confidence: 94%
“…Recently, the significant reduction of E-cadherin by regulation of HPV-16 E6 and/or E7 in cervical cell lines has been demonstrated extensively by many studies [28,29]. Furthermore, Haga et al also found that ectopic expression of HPV-16 E6 and E7 in normal epithelial cells in vitro resulted in decreased expression of E-cadherin and increased expression of N-cadherin although N-cadherin was not at readily detectable levels [30]. We therefore evaluated whether HR-HPV E6 and E7 could regulate cadherin switch in cervical cancer and contribute to tumor progression.…”
Section: Discussionmentioning
confidence: 98%
“…In non-cochlear tissues, adhesion proteins have been implicated in mediating signaling pathways in various pathological conditions, including cell detachment (Frisch and Screaton, 2001; Grossmann, 2002; Haga et al, 2008; Malik, 1997). The detachment of cells from their anchorage has been shown to be a trigger for apoptosis (Frisch, 2000).…”
Section: Introductionmentioning
confidence: 99%